Whole-body stability control with high contact redundancy for wheel-legged hexapod robot driving over rough terrain. (March 2023) - Xu, Kang; Lu, Yanqun; Shi, Lei; Li, Jianyong; Wang, Shoukun; Lei, Tao
Highlights: An electric parallel wheel-legged hexapod robot is proposed. An event-based disturbance control is presented to detect the disturbances. A whole-body stability control is employed to stabilize the posture. Our robot with the proposed methods can be applied to carry load stably. Abstract: Maintaining a stable trunk while driving over rough terrain is a challenging issue for a multi-wheel-leg mobile robot, since the control coupling between the legs and the trunk has a strong negative effect on the robot's stability. Particularly, the relevant works on the wheel-legged hexapod robot are not available. In this paper, we propose a novel event-based disturbance control together with whole-body stability control, which enables contact-redundancy hexapod robot to stably drive over rough terrain. For highly redundant contact with the ground, the event-based disturbance control is employed for the robot to accurately detect the disturbed leg(s). The whole-body stability control, utilizing model predictive control to achieve the optimal ground reaction force profiles as a feedforward command to the leg-level controller and rendering robot attitude decoupling on computing the desired generalized position, velocity, and acceleration of legs, is proposed to suppress the external disturbances and to stabilize the trunk's posture. To validate the proposed methods, a series of experimental trials, along with comparative evaluations, are carried out on a wheel-legged hexapod robot.